Joint Tracking Method for the Unresolved Decoy and Target with Monopulse Radar - Su Jian; Song Zhi-yong; Fu Qiang; Long Zhao-fei (Leida xuebao, 2015)
The Miniature Air Launched Decoy (MALD) flies cooperatively with a true target and construct unresolved targets within the radar beam. The unresolved targets and decoy result in echoes aliasing and observation merging, which causes serious measurement error and traditional track processing failure. Based on the analysis of jamming patterns and characteristics, the signal model of the unresolved targets is proposed. Combining jamming detection, echoes observation, and likelihood function characteristics, the proposed approach directly operates on the monopulse sum and difference returns and uses the particles propagating and evolving in the state space to obtain the conditional state probability density of the unresolved targets and decoy. This method effectively bypasses measurement extraction and parameter measurement, and realizes the joint tracking of the target and decoy. Furthermore, it provides the necessary conditions for target selection to the radar based on track and trajectory data. Simulation experiments illustrate the effectiveness of the proposed method.